2011
DOI: 10.4236/jbpc.2011.23028
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of immunity by some pesticides, xenobiotics, and industrial chemicals. <i>In vitro</i> model

Abstract: In recent years, attention has focused on suppression of immunity in immunocompromised patients. The definition of immunocompromise is impairment of the immune system caused by a disease or treatment. In addition to disease and treatment, other factors such as exposure to pesticides or toxic chemicals can damage the immune system. An in vitro test was used to assess the ability of monochloroacetic acid (MCA) (CAS number 79-11-8), dichloroacetic acid (DCA) (CAS number 79-43-6), trichloroacetic acid (TCA) (CAS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Lysozyme, besides its medical application, is used in the study of the toxicity of pesticides and suppression of immunity by different pesticides [27]. Lysozyme is a glycoside hydrolase enzyme that normally catalyzes the hydrolysis of 1,4-beta linkages between N-acetylmuramic acid and N-acetyl-D-glucosamine residues in peptidoglycan, which is the major component of gram-positive bacterial cell walls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysozyme, besides its medical application, is used in the study of the toxicity of pesticides and suppression of immunity by different pesticides [27]. Lysozyme is a glycoside hydrolase enzyme that normally catalyzes the hydrolysis of 1,4-beta linkages between N-acetylmuramic acid and N-acetyl-D-glucosamine residues in peptidoglycan, which is the major component of gram-positive bacterial cell walls.…”
Section: Resultsmentioning
confidence: 99%
“…Lysozyme is a glycoside hydrolase enzyme that normally catalyzes the hydrolysis of 1,4-beta linkages between N-acetylmuramic acid and N-acetyl-D-glucosamine residues in peptidoglycan, which is the major component of gram-positive bacterial cell walls. However, it was shown that lysozyme can be active also against gram-negative bacterial cells by hydrolysis of links in LPS if detergents such as synthetic EDTA, or natural taurine or gal acids have been added [27]. Active lysozyme with purity more than 95.5% was isolated in the chromatographic experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The OP pesticides belong to this group of substances. Pesticides often have other unpredicted toxic side effects [8].…”
Section: At the Beginningmentioning
confidence: 99%
“…In [8], the suppression of immunity by some pesticides and their equally harmful consequences for human health generally are discussed. Several other chemicals can cause psychosis.…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…Inadequate host defense may result in serious infections, as is sometimes seen in immunocompromised hosts. It is especially important in the case of immunocompromised persons such as those who have been infected with human immunodeficiency virus (HIV), diabetic persons or those intoxicated by chemicals [18]. Hyperforin is a very powerful antibiotic against the Coccaceae family of bacteria, including Streptococcus pneumoniae, Neisseria gonorrhoeae and N. meningitidis, which contain both antibiotic-sensitive and multiple-antibiotic-resistant species [10].…”
Section: Introductionmentioning
confidence: 99%